Makna Independent Living Bagi Penyandang Disabilitas - Dina Alamianti (Dialektika, 2018)
This study discusses independent living for persons with disabilities in Bandung Independent Living Center, Bandung. The research methods using qualitative research with the tradition of phenomenology. The collection of data obtained through observation, in-depth interviews, and documentation study. The result of the research showed independent living understood as a concept and action which are considered professional with disabilities in term of persons with disabilities in other words they know and understand their needs. Disabled interpret live independently because they mind so as to create a strategy.